2010
DOI: 10.1111/j.1540-5826.2010.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Acquired Mentoring Relationships and Young Adult Outcomes Among Adolescents with Learning Disabilities

Abstract: We evaluated whether having a naturally acquired mentor during adolescence was associated with improved adult outcomes among youth with learning disabilities (YLD). Mentored youth were more likely to have graduated from high school, reported a higher level of self‐esteem, and reported a higher overall number of positive outcomes than nonmentored youth. Mentorship by teachers/guidance counselors was associated with larger differences in high school graduation rates and self‐esteem compared to nonmentored youth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 36 publications
0
26
1
Order By: Relevance
“…An exception is the growing recognition of the benefits of peer support for individuals with psychiatric disabilities, including increased self-advocacy and quality of life (Chinman, et al, 2014;Gidugu et al, 2014). This recognition, combined with the limited, yet positive evidence for the population as a whole, indicates that the impact of mentoring for individuals with disabilities is consistent with the larger body of work on mentoring (Ahrens et al, 2010;Bell, 2012;Britner et al, 2006;Rhodes & Lowe, 2009).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…An exception is the growing recognition of the benefits of peer support for individuals with psychiatric disabilities, including increased self-advocacy and quality of life (Chinman, et al, 2014;Gidugu et al, 2014). This recognition, combined with the limited, yet positive evidence for the population as a whole, indicates that the impact of mentoring for individuals with disabilities is consistent with the larger body of work on mentoring (Ahrens et al, 2010;Bell, 2012;Britner et al, 2006;Rhodes & Lowe, 2009).…”
Section: Introductionmentioning
confidence: 75%
“…One population that historically has had limited participation in mentoring programs is individuals with disabilities, resulting in relatively few studies on the impact of mentoring for this population (Ahrens, Dubois, Lozano, & Richardson, 2010;Bell, 2012;Britner et al, 2006;Shpigelman & Gill, 2012;Stumbo, Blegen, Lindahl-Lewis, 2008). An exception is the growing recognition of the benefits of peer support for individuals with psychiatric disabilities, including increased self-advocacy and quality of life (Chinman, et al, 2014;Gidugu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have also shown that students who have learning disabilities are at risk of responding to their difficulties in non-productive ways, such as passively giving up (Firth, Frydenberg, & Greaves, 2009;Lackaye, Margalit, Ziv, & Ziman, 2006;Nu´n˜ez et al, 2005;Sideridis, Morgan, Botsas, Padeliadu, & Fuchs, 2006), avoiding the problem (Singer, 2007), engaging in disruptive behaviour (Chan & Dally, 2000;Prior, 1996) and social withdrawal (Bryan, 2005;Kotzer & Margalit, 2007), resulting in increased risk of school dropout (Deshler, 2005;Scanlon & Mellard, 2002), juvenile delinquency (Ahrens, DuBois, Lozano, & Richardson, 2010;Svetaz, Ireland, & Blum, 2000), social isolation (Bryan, Burstein, & Ergul, 2004;Svetaz et al, 2000) and depression (Ahrens et al, 2010;Wilson, Armstrong, Furrie, & Walcott, 2009). …”
Section: Introductionmentioning
confidence: 97%
“…Conversely, social skill deficits in older students with LDs may heighten awareness of their own disability due to their own struggles when comparing themselves to their peers. This comparison may be especially frustrating if they do not have a full understanding of how to effectively manage their disability, thus negatively impacting their self-esteem and interactions with others (Ahrens et al 2010;Alesi et al 2012;MacMaster et al 2002). Abernathy and Taylor (2009) compared LD self-awareness to a person understanding their medical condition.…”
mentioning
confidence: 94%
“…Specifically, when someone knows their medical condition, they are able to take appropriate measures to manage their condition and understand how it can impact their life. The responsibility of teaching and mentoring a child about their disability often falls on the parent, teacher, or other related education professionals (Ahrens et al 2010;Higgins et al 2002). As such, it is important to emphasize the benefits of providing appropriate and effective methods of teaching children with LD to better understand their learning difficulties.…”
mentioning
confidence: 99%